The ancient novel and beyond - Panayotakis, Stelios, 1968-; Zimmerman, M.; Keulen, Wytse Hette. (Mnemosyne, Supplements, 2003)
This volume comprises the revised versions of selected papers read at the International Conference on the Ancient Novel (Groningen, July 2000). The papers cover a wide range of scholarly issues that were prominent in the programme of the conference, and feature the most recent approaches to research on the ancient novel. The essays combine judicious use of literary theory with traditional scholarship, and examine the ancient novels and related texts, such as Oriental tales and Christian narrative, both in their larger, literary, cultural and social context, and as sources of inspiration for Byzantine and modern fiction. This book is important not only for classicists and literary historians, but also for a general public of those interested in narrative fiction.